PENGARUH ATRIBUT HOTEL DAN KARAKTERISTIK SOSIAL DEMOGRAFI WISATAWAN PADA PEMILIHAN HOTEL DI BALI - Erry Setiawan (STIE Mahardhika, 2020)
Predicting the factors that influence the selection of hotels by tourists is a difficult task as some variables affect it. Therefore, the ability of hospitality businesses to control their hotel preferences requires a comprehensive understanding of both tangible (physical facilities, equipment, staff and communication equipment) and intangibles (employee service skills and skills, safety levels, materials that can attract and influence visitor choice). This quantity study explores the influence of hotel attributes and socio-demographic traveller on the selection of hotels in the metropolitan city of Bali to help hotels that have an analytical understanding of hotel attributes that influence hotel choice. With a modified survey built from a previous study, data from 322 travelers was taken from seven carefully selected hotels in the study area through probability sampling. Analysis of the data showed that 67 percent of adopted hotel attributes were critical in the selection of hotels for tourists. The average hotel attributes are safety/safety (3.41), live music/live entertainment (3.35), sustainable power plants (3.21), hotel cleaning (3.17), quality in-room amenities (3.16), free internet service (3.11) and employee behavior (3.10), as interpreted by respondents. Multiple Regression Analysis (MRA) results to test the influence of socio-demographic characteristics of hotel selection respondents at 0.05 showed that religion, popular residence as travelers and respondents' income influenced their preference for hotel attributes. By comparison, the gender, age, marital status, occupation and educational achievement of respondents had no effect on their hotel attributes. One of the main recommendations of the study is that hospitality businesses should evaluate travellers' opinions about their hotel attributes regularly. This is important for the satisfaction of the guests. In turn, increased guest satisfaction, which is important for business in this highly competitive market, and other advantages of offering suitable services to guests can be achieved..